f (x) = ex
⇒ f’(x) = ex
Now, if f’(x) = 0, then ex = 0.
But, the exponential function can never assume 0 for any value of x.
Therefore, there does not exist c ϵ R such that f’(c) = 0
Hence, function f does not have maxima or minima.
Rate this question :
If the sum of theMathematics - Board Papers
A metal box withMathematics - Board Papers
Show that aRD Sharma - Volume 1
Find the local maMathematics - Board Papers
Prove that the seMathematics - Board Papers
Prove that the raMathematics - Board Papers
Prove that the leMathematics - Board Papers